Xanthoma verruciformis of the gingiva: case report - Millán-Golindano, Carlos (2023)
Oral verruciform xanthoma is a benign inflammatory lesion of unknown etiology. It is a reactive, non-tumorous lesion affecting the oral mucosa, the semi-mucosa, and the skin of the extremities. Its clinical presentation consists of a single, elevated lesion with an irregular surface. Its microscopic characteristic is the accumulation of lipid-containing macrophages in the papillae of the connective tissue between the epithelial ridges. This report reviews the literature and presents a case of this pathology. The patient is an 11-year-old female who came for consultation with her guardian. Clinically, a single pale pink lesion approximately 4 mm in length, oval in shape with defined borders, rough, keratinized surface, firm consistency, and a base adhered to the tissue was observed. An excisional biopsy and histopathological study were performed. In conclusion, the diagnosis of verruciform xanthoma is complex. Despite being a benign lesion, it can be confused with other malignant differential diagnoses. Therefore, we recommend evaluating the patient's medical history, risk factors, and establishing an accurate treatment plan.